Employing a Customer Orientation to Foster Entrepreneurial Behaviour in the Workplace - Wickland, Juliane (2013)
Employees’ entrepreneurial behaviour provides a competitive advantage for firms. Individual entrepreneurship research has looked mostly at the interaction with the firm-level construct or at organisational antecedents for entrepreneurial behaviour. The individual personal aspects that contribute to developing the behaviour present a gap in the current literature. This paper aims to fill this gap and argues that customer orientation, as a psychological variable, has an impact on the display of entrepreneurial behaviour. Based on the literature, this paper builds and tests an exploratory relationship model. This model includes helping behaviour as a distinct organizational citizenship behaviour, which has previously been linked to customer orientation and is argued to impact entrepreneurial behaviour as well. In addition, the impact of national workplace culture on the three employee-level variables has been investigated. The hypotheses were built based on the literature and tested via one-way ANOVA and mediated regression analysis using an international sample of 262 professionals from Germany, Malaysia, and the U.S.A., which was collected via an online survey. The findings reveal that customer orientation positively relates to entrepreneurial behaviour. Helping behaviour partially mediates this relationship. It was revealed that employees in the U.S. exhibit significantly higher levels of helping behaviour and entrepreneurial behaviour. There was no significant difference between Malaysia and Germany evident for these behaviours. Customer orientation did also not vary based on national workplace. The findings add to the existing entrepreneurship, customer orientation and organizational citizenship behaviour literature and provide practical implications for fostering entrepreneurial behaviour in existing firms.